Industry Payments During the COVID-19 Pandemic to Cardiologists in the United States - Anju Murayama; Sae Kamamoto; Haruki Shigeta; Akihiko Ozaki, MD, PhD (CJC Open, 2023)
In the US, research has established that a funding relationship exists between pharmaceutical industries and physicians, particularly cardiologists. This study aimed to fill a research gap via an in-depth data analysis of the impact that the coronavirus 2019 restrictions had on this dynamic. The payments per cardiologist declined by 55.7% (95% confidence interval: 52.0%‒-59.0%, P < 0.001) in monetary amounts, and by 66.6% (95% confidence interval: 66.1%-67.1%, P < 0.001) in the number of payments right after the COVID-19 pandemic onset, respectively. Cardiologists must consider the ethical implications of the potential for their clinical practice to be influenced by industry payments. Résumé: Aux États-Unis, la recherche a établi l’existence d’une relation de financement entre l’industrie pharmaceutique et les médecins, particulièrement les cardiologues. Cette étude visait à combler une lacune dans la recherche grâce à une analyse approfondie des données concernant les répercussions des restrictions relatives à la COVID-19 sur cette dynamique. Les rétributions versées par cardiologue ont baissé de 55,7 % (intervalle de confiance [IC] à 95 % : 52,0 % à 59,0 %, p < 0,001) en argent et de 66,6 % (IC à 95 % : 66,1 % à 67,1 %, p < 0,001) en nombre de versements, juste après le début de la pandémie de COVID-19. Les cardiologues doivent considérer les implications éthiques liées à l’influence potentielle de ces versements sur leur pratique.